Morphological changes in Harderian glands after the implantation of polycaprolactone films into the cornea; Перспективы развития фундаментальных наук; Т. 4 : Биология и фундаментальная медицина - Filippova E. O. Ekaterina Olegovna (2022, 2022)
Заглавие с экрана